First Experience Using the Sheathless Hyperion Guiding Catheter System Designed for Direct Insertion - Andrew Borrie; Sarah Fairley; Scott A. Harding (Journal of Interventional Cardiology)
Background. Use of sheathless guiding catheters for transradial PCI has the potential to reduce radial trauma and allow use of larger catheters to facilitate complex PCI. The new sheathless Hyperion guide catheter (SHGC) system allows direct insertion of the SHGC using a 20G needle or IV cannula, a 0.025″ Silverway wire, and a dilator. We report the first clinical experience. Methods. We prospectively evaluated outcomes in consecutive patients undergoing PCI using radial access and the SHGC catheter at our institution between June 2020 and June 2021. There were no exclusion criteria. Results. The study included 120 patients, mean age 67 ± 12.6 years, 79.2% male. Insertion of a SHGC was attempted in 128 radial arteries and was successful in all cases. The SHGC was inserted directly in 74 (57.8%), following initial sheath removal in 24 (20.5%) and through the initial sheath in 30 (26.2%). Coronary artery engagement with a SHGC was successful in 126 (98.4%). A total of 150 lesions were treated, the majority being complex: 16.1% chronic total occlusions, 37.1% calcified, 30.6% bifurcation, and 43.5% long lesions. Angiographic success was achieved in 149 (99.2%) lesions. Periprocedural myocardial infarction occurred in 5 (4.2%) patients. There was no in-hospital urgent revascularisation or death and no major bleeding or vascular complications. Occlusion occurred in 2 (1.6%) radial arteries. Conclusion. This first clinical experience with the SHGC demonstrates that direct insertion is safe and effective and that the use of the SHGC allows complex interventions to be undertaken transradially with a high success rate.